Teori Kedatangan Islam di Asia Tenggara: Analisis Kritis terhadap Kekuatan dan Kelemahan Masing-Masing Teori - Putri Arafat, Marsya; Arafat, Marsya Putri; Nadiyah, Asma; Adam Rizki Rahman; Nelly Yusra (Tanjak: Sejarah dan Peradaban Islam, 2026)
This article presents a critical analysis of various theories concerning the arrival of Islam in Southeast Asia, namely the Gujarat Theory, the Arab/Makkah Theory, the Persian Theory, the Chinese Theory, and the Bengal Theory. The study aims to evaluate the strengths and weaknesses of each theoretical argument and to synthesize a more comprehensive understanding of the complexity of the Islamization process in the region. This research employs a literature review method using a comparative critical analysis approach to relevant historical sources. The findings reveal that each theory offers valuable contributions while also possessing certain limitations. The Gujarat Theory is strong in terms of archaeological evidence but weak in terms of chronology and religious alignment. The Arab/Makkah Theory demonstrates strong validity in terms of historical timeline and the similarity of the Shafi‘i school of thought as the origin of Islamic teachings, although it lacks early physical evidence. Meanwhile, the Persian and Chinese theories effectively explain cultural aspects, architectural influences, and the role of intermediary agents in the processes of dissemination and acculturation. It is concluded that the arrival of Islam in Southeast Asia was complex, gradual, and multidimensional. Islam initially came from Arab/Makkah, was subsequently reinforced by Gujarati traders, enriched by Persian cultural influences, and supported by the active role of Chinese communities. The existing controversy is primarily due to differences in analytical focus rather than the absolute validity or invalidity of any single theory. Therefore, these theories should be understood as complementary, collectively forming a holistic picture of the peaceful and multi-actor process of Islamization in Southeast Asia.